QDOT MICRO versus THERMOCOOL SMARTTOUCH and THERMOCOOL SMARTTOUCH Surround Flow in radiofrequency ablation of paroxysmal atrial fibrillation - Jose Osorio; Sonia Maccioni; Reecha Sharma; Leena Patel; Paul Spin; Andrea Natale (Becaris Publishing Limited, 2023)
Aim: The objective of this study was to indirectly compare QDOT MICRO™ (QDOT), Thermocool R SmartTouch™ (ST) and Thermocool R SmartTouch R Surround Flow (STSF) to treat paroxysmal atrial fibrillation. Methods: Differences in baseline characteristics between study cohorts were reduced by reweighting patients using inverse probability of treatment weighting. The primary outcome was procedure time. Secondary outcomes were fluoroscopy time, clinical success at 12 months, and rhythm monitoring-adjusted recurrence. Results: QDOT was associated with significantly faster mean procedure and fluoroscopy time, and significant improvement in the rate of recurrence compared with pooled ST/STSF. No difference was observed for clinical success at 12 months. Conclusion: QDOT was associated with greater efficiency, greater effectiveness in rhythm monitoring-adjusted recurrence and similar effectiveness in clinical success at 12 months compared with pooled ST/STSF.